Ghostwriting: Simulacra of Academic Performance - S. A. Sheypak (Высшее образование в России)
The article is a book review on “Ethnography of Bogus. Who and how writes customized academic essays in Russia” by A. Davydov and P. Abramov (Moscow: Khamovniki Foundation for Social Research: Common Place, 2021, 176 p.). This book describes the practices of contract cheating in Russian higher education as an established social institution involving undergraduate and graduate students. “Ethnography of Bogus” presents the faculty staff only as a resource for the market of ghostwriting: an explicit resource when teachers of higher education become ghostwriters, or an implicit resource, when formalist assessment mechanisms of student work contribute to the development of ghostwriting practices. The description of ghostwriting practices in the study reveals the decline of the concept of research advisor for undergraduate and graduate students, due to the precarity of teachers in higher education. The decline is incited by mass student entry policy and efficient management mechanisms of higher education institutions. As a result, the students who turn to contract cheating in a regular manner do not develop professional and academic skills appropriate to an undergraduate or graduate degree. The students develop their soft skills required in interactions with ghost-writers when they negotiate the terms of contract cheating as customers of writing services.